Video compression handbook - Beach, Andy; Owen, Aaron (Peachpit Press, 2019)
More than ever, video and preparing it for delivery is a critical part of many jobs. One of the keys to delivering a high-quality video experience is understanding the fundamentals of video and video compression. Video Compression Handbook gives you these keys by explaining the core concepts of compression, the latest tools to use, and the important workflows for creating video for specific deliveries. After the groundwork is laid, you will learn how to compress video according to the specific requirements of your projects and will learn some best practices by following the author's own tips and recipes. Experts in the field lend their own solutions in several sidebars throughout the book, making this a valuable learning tool for anyone learning to encode video, whether you are a video editor, independent filmmaker, or simply involved in the video-to-viewer process.